2013
DOI: 10.1002/etc.2379
|View full text |Cite
|
Sign up to set email alerts
|

Variations in lethal and sublethal effects of cypermethrin among aquatic stages and species of anuran amphibians

Abstract: Despite the use of model species to predict the effects of chemicals in the environment, unpredicted variation in levels of risk to organisms from xenobiotics can be observed. Physiological and morphological differences between species and life stages may lead to differences in sensitivity, while seasonal and spatial variation in pesticide concentrations may affect the level of risk faced by organisms in the environment. Because anurans breed in aquatic habitats subject to contamination by runoff and spraying,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
19
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 46 publications
2
19
0
Order By: Relevance
“…Likewise, metamorphs of the European moor frog (Rana arvalis), which were chronically exposed to another insecticide (a-cypermethrin) (Greulich and Pflugmacher, 2003) and metamorphs of four North American anurans (Lithobates [Rana] clamitans, Lithobates [Rana] pipiens, Lithobates sylvaticus [R. sylvatica], Anaxyrus [Bufo] americanus), which were chronically exposed to glyphosate-based herbicides (Howe et al, 2004) showed decreased SVL. Comparable to our results, also Biga and Blaustein (2013) did not observe effects on body length when larvae of North American Pseudacris regilla, Rana cascadae and Rana aurora were exposed to a sublethal insecticide (cypermethrin) concentration at early and late developmental stages. Exposure of eggs and newly hatched individuals of R. arvalis to sublethal carbaryl concentrations shortened time to metamorphosis, whereas chronic exposure prolonged it (Greulich and Pflugmacher, 2003).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Likewise, metamorphs of the European moor frog (Rana arvalis), which were chronically exposed to another insecticide (a-cypermethrin) (Greulich and Pflugmacher, 2003) and metamorphs of four North American anurans (Lithobates [Rana] clamitans, Lithobates [Rana] pipiens, Lithobates sylvaticus [R. sylvatica], Anaxyrus [Bufo] americanus), which were chronically exposed to glyphosate-based herbicides (Howe et al, 2004) showed decreased SVL. Comparable to our results, also Biga and Blaustein (2013) did not observe effects on body length when larvae of North American Pseudacris regilla, Rana cascadae and Rana aurora were exposed to a sublethal insecticide (cypermethrin) concentration at early and late developmental stages. Exposure of eggs and newly hatched individuals of R. arvalis to sublethal carbaryl concentrations shortened time to metamorphosis, whereas chronic exposure prolonged it (Greulich and Pflugmacher, 2003).…”
Section: Discussionsupporting
confidence: 88%
“…Significantly elevated mortality at metamorphosis after exposure of different developmental stages to sublethal insecticide (carbaryl) concentrations was also observed in Southern leopard frogs (Lithobates sphenocephalus [Rana sphenocephala]) (Bridges, 2000). Biga and Blaustein (2013) observed species-specific effects on survival when different aquatic life stages of three North American anurans (P. regilla, R. cascadae and R. aurora) were exposed to sublethal concentrations of another insecticide (cypermethrin). These authors did not observe increased mortality in animals of any species exposed during embryonic development, but in R. cascadae when exposed at early and in P. regilla when exposed at early and late larval stages.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…In addition to the loss of habitats in agricultural areas, agrochemical pollution, which often interacts with other factors like climate change, UV-B radiation, emerging infectious diseases and alien species (Collins and Storfer, 2003;Stuart et al, 2008), is detrimental to amphibians (Mann et al, 2009). The impacts of agrochemicals on amphibians in water bodies (Xu and Oldham, 1997;Relyea, 2009;Biga and Blaustein, 2013) and on land Mann and Bidwell, 1999;Marco et al, 2001;Howe et al, 2004;Cauble and Wagner, 2005;Relyea, 2005;Bernal et al, 2009;Dinehart et al, 2009;Belden et al, 2010;Brühl et al, 2013) have been thoroughly studied and documented (Govindarajulu, 2008;Mann et al, 2009;Relyea, 2011;.…”
mentioning
confidence: 99%